2015
DOI: 10.1016/j.wem.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Outbreaks Among Colorado River Rafters in the Grand Canyon, Summer 2012

Abstract: The results suggest that norovirus may have been introduced by ill or asymptomatic individuals actively shedding the virus in their vomitus or feces, and spread within, or between, river trips by different modes of transmission. This study reinforces the importance of appropriate guidance and practice regarding norovirus prevention and the necessity of postoutbreak containment in relatively isolated groups of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Despite the clear role of vomiting in transmission, there is very little data on viral loads in emesis. An investigation of norovirus outbreaks among rafters in the Grand Canyon detected GI norovirus in a vomitus sample [ 20 ]. In samples collected during a GI.1 Norwalk virus human challenge trial, 56% of emesis samples had detectable virus and the median titer was 4.1x10 4 gEq/ml [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the clear role of vomiting in transmission, there is very little data on viral loads in emesis. An investigation of norovirus outbreaks among rafters in the Grand Canyon detected GI norovirus in a vomitus sample [ 20 ]. In samples collected during a GI.1 Norwalk virus human challenge trial, 56% of emesis samples had detectable virus and the median titer was 4.1x10 4 gEq/ml [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Magill-Collins et al 2015, screening of the presence of norovirus-RNA in the toilet solid waste samples using RT-qPCR demonstrated that one sample tested positive for GI and the other samples were positive for GII (no GI/GII coinfection was observed), while GIV was not detected from any samples (Magill-Collins et al 2015). This result is consistent with other clinical studies on norovirus, which reported that GII accounts for the large majority of reported outbreaks and GI makes up the majority of the remaining cases, whereas GIV strains have rarely been detected from patients.…”
Section: Textmentioning
confidence: 51%
“…Norovirus outbreaks among the Colorado River rafters in the Grand Canyon have been reported in the last few decades (Jones et al 2009;Malek et al 2009). In summer 2012, we experienced large recurrent gastroenteritis outbreaks among the Colorado River rafters and recently reported the results of our epidemiological investigation (Magill-Collins et al 2015).…”
Section: Textmentioning
confidence: 62%
See 1 more Smart Citation
“…Rafters exposed to waters which drain large amounts of mountain streams are therefore at high risk of developing infection [18]. In addition there have been several norovirus outbreaks during whitewater rafting trips, presumably as travelers are close together, lack indoor plumbing and hand hygiene [19,20]. Travelers should be advised to bring soap for washing hands and ensure adequate water filtration if going on a rafting excursion.…”
Section: Whitewater Sportsmentioning
confidence: 99%